Ethosomal Gel for Improving Transdermal Delivery of Thymosin β-4 - Fu, Xianglei (Int J Nanomedicine, 2019)
PURPOSE: Thymosin β-4(Tβ-4) is a macromolecular protein drug with potential for drug development in wound repair but is limited by the shortcomings of macromolecular protein, such as large volumes, poor membrane permeability, and unstable physicochemical characteristics. Ethosomes could enhance cell membrane fluidity and reduce epidermal membrane density to make macromolecular drugs through the stratum corneum into the deeper layers of the skin easily. Herein, we developed and characterized a novel transdermal delivery vehicle to load macromolecular protein peptides and use Tβ-4 as a model drug wrapped into ethosomes. METHODS: We used the orthogonal method to optimize the formulation of the ethosome preparation prepared by the ethonal infusion method. Ethosomal gels were characterized by using different analytical methods. Transdermal release rate in vitro have been demonstrated in Franz diffusion cells and the efficacy of drug-loaded nanocarriers in vivo was investigated in a mouse model. RESULTS: Optimized Tβ-4 ethosomal gels have good physicochemical properties. The drug amounts of the cumulative release in the ethosomal gel within 5 hours were 1.67 times that of the T-β4 gel in vitro release study, and the wound healing time of ethosomal gel group was only half of the T-β4 gel group in vivo pharmacokinetic study. Compared with the free drug group, the ethosome preparation not only promotes the percutaneous absorption process of the macromolecular protein drugs but also shortened wound recovery time. CONCLUSION: Hence, we provide a possible good design for ethosomal gel system that can load macromolecular protein peptide drugs to achieve transdermal drug administration, promoting the percutaneous absorption of the drug and improving the effect.